2022
DOI: 10.1097/brs.0000000000004476
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Addressing Malalignment in Revision Surgery for Proximal Junctional Kyphosis Following ASD Surgery

Abstract: Study Design. Retrospective cohort study. Objective. Understand the benefit of addressing malalignment in revision surgery for proximal junctional kyphosis (PJK). Summary of Background Data. PJK is a common cause of revision surgery for adult spinal deformity patients. During a revision, surgeons may elect to perform a proximal extension of the fusion, or also correct the source of the lumbopelvic mismatch. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Passias et al showed failure to optimize sagittal alignment at the time of revision surgery for PJK led to worse clinical outcomes compared with patients who had their abnormal lumbopelvic mismatch corrected in combination with proximal extension of the fusion construct and showed increased rates of PJK and PJF in the malaligned group. 63 It is also unlikely that biomechanical prophylactic strategies designed to prevent PJK and PJF will be able to offset significant errors in alignment, rendering health care dollars utilized in their deployment futile.…”
Section: Alignment/planningmentioning
confidence: 99%
“…Passias et al showed failure to optimize sagittal alignment at the time of revision surgery for PJK led to worse clinical outcomes compared with patients who had their abnormal lumbopelvic mismatch corrected in combination with proximal extension of the fusion construct and showed increased rates of PJK and PJF in the malaligned group. 63 It is also unlikely that biomechanical prophylactic strategies designed to prevent PJK and PJF will be able to offset significant errors in alignment, rendering health care dollars utilized in their deployment futile.…”
Section: Alignment/planningmentioning
confidence: 99%
“…For recurrent PJK/F, surgical options become limited because of the little room for proximal extension and alignment correction, with clinical and financial burden. 7,8 Therefore, preventing the recurrence of this complication during the initial revision is vital.…”
mentioning
confidence: 99%